The Role Of Urban Density And Morphology In The Air Pollution Of Tehran Metropolitan - ROUHOLLAH OSHRIEH; EHSAN VALIPOUR (Journal of Contemporary Urban Affairs, 2019)
Today, regard for the wellbeing of the group and the earth is on the plan of most nations on the planet, and one of its imperative viewpoints is the contamination of the air and figuring out how to diminish it. Without a doubt, a standout amongst the most vital ranges that assume an unequivocal part in decreasing or expanding this parameter is the city and urban morphology. Tehran, which is viewed as the capital and vital city of Iran, has experienced this issue for a long time, and there are no legitimate arrangement found to decrease its air contamination. Then again, the city has movement from different parts of the nation consistently that makes this issue harsher. The most vital issue in such manner is the city's range, and in addition, the city's extension, which decides the thickness of the city.  The failure of the vast majority to purchase houses inside the city has made satellite towns nearby Tehran. Then again, the presence of tremendous local locations around Tehran and the area of workplaces in the downtown area are among alternate issues tended to in this investigation. This examination endeavoured to utilize the explanatory expressive technique to think about the part of pressure and morphology of Tehran and its effect on the air contamination and give answers for diminishing air contamination and movement.